Disease-free survival as a surrogate for overall survival in upper tract urothelial carcinoma - Fajkovic, Harun; Cha, Eugene K.; Xylinas, Evanguelos; Rink, Michael; Pycha, Armin; Seitz, Christian; Bolenz, Christian; Dunning, Allison; Novara, Giacomo; Trinh, Quoc-Dien; Karakiewicz, Pierre I.; Margulis, Vitaly; et al. (World journal of urology, 2013)
The primary endpoint in trials of perioperative systemic therapy for urothelial carcinoma is 5-year overall survival (OS). A shorter-term endpoint could significantly speed the translation of advances into practice. We hypothesized that disease-free survival (DFS) could be a surrogate endpoint for OS in upper tract urothelial carcinoma (UTUC) patients treated with radical nephroureterectomy (RNU).
Gesehen am 31.03.2022